(untitled) (Human Factors in Design, 2025)
The ergonomic workspace analysis (EWA) aims to intervene in the productive environment to analyze the problems and the physical and psychophysiological consequences resulting from work. Within this context, the objective of this study was to carry out an ergonomic analysis of work in a beautician’s workplace. The demand was identified based on the report of a beautician about her discomfort and pain after performing eyebrow shaping on customers. For data collection, an on-site observation of the activity was carried out with the application of a focused questionnaire, image recordings and completion of a body map, which indicates the location, duration, frequency and intensity of the musculoskeletal discomfort. In parallel, the RULA postural analysis protocol was applied, which indicated level 7 (high risk of injury). Through data analysis, postural recommendations were given, and if applied, they would decreased the RULA level to 4 (low risk of injury).